C-reactive protein elevation ratio as an early predictor of postoperative severe complications after laparoscopic gastrectomy for gastric cancer: a retrospective study - Hiroaki Tanaka; Tatsuro Tamura; Takahiro Toyokawa; Kazuya Muguruma; Naoshi Kubo; Katsunobu Sakurai; Masaichi Ohira (BMC Surgery, 2019)
Abstract Background In gastrectomy, postoperative elevation of C-reactive protein (CRP) is thought to be useful for predicting complications. Laparoscopic gastrectomy (LG) is less invasive than laparotomy and the elevation of CRP is also mild. Postoperative complications such as anastomotic leakage not only increase the severity of the condition, but also carry a poor prognosis when treatment is delayed. Early treatment is therefore necessary. Method This retrospective study examined the relationship between occurrence of complications and the ratio of CRP levels on postoperative days 1 and 3 (CRP ratio) for 449 gastric cancer patients who underwent LG in the Department of Gastrointestinal Surgery at Osaka City University Hospital between 2006 and 2016. Results We observed that factors associated with postoperative complications were preoperative renal failure and CRP ratio. No significant associations with surgical procedure, operation time, bleeding volume, age, obesity, measured CRP concentration, or white blood cell count were evident. The optimal cut-off for CRP ratio to predict postoperative complications from the receiver operating characteristic curve was 2.13. Conclusion Our results suggested that the risk of severe postoperative complications after LG could be predicted using the CRP ratio.